Rancang Bangun Aplikasi Toko Kaum Jaya Berbasis Website - Johan Toni Wijaya; Dadang Yusup; Intan Purnamasari (Peneliti.net, 2023)
The Kaum Jaya store is a shop that sells typical Karawang food and drinks which has been established since 2017 and located at Jl. HS.Ronggo Waluyo, Puseurjaya, Telukjambe Timur, Karawang, West Java. Kaum Jaya store does not have branches and online system. Based on this background, it’s necessary to create an application that would simplify transaction activities with online payment systems and providing information to customers about what products are in the Kaum Jaya store. The name of application is Kaum Jaya. Application development is carried out using the prototype method. In its development, the application uses web technologies such as HTML, CSS, PHP, JavaScript, and MySQL to store product, order and user data. This application can be accessed via browser on computers and mobile devices. The result of this program is the creation of a website-based application that has passed the testing stage. This application is also equipped with a transaction system assisted by midtrans and will store all transaction history data. With the application, hope that it can provide convenience for customers in purchasing Kaum Jaya store products online, as well as simplify products and order management for store owners